Disability disclosure in healthcare settings for individuals with developmental disabilities: A qualitative study of patient and caregiver perspectives - Ashley Falcon; Andrew Porter; Brady Wallace; Jenna Tatavitto; Gillian Aaronson; Arnina Wiles; Rachel Ryan; Lindsey Rosenbloom (PLoS ONE, 2025)
Background People with disabilities experience significant healthcare disparities, including missed opportunities for preventive, inaccessible services, and inadequate communication with providers. These challenges often lead to unmet healthcare needs and poor health outcomes. Disability disclosure is one strategy that may aid in closing this healthcare equity gap, though limited research sheds light on patient and caregiver feelings towards and preferences for disclosure. Objective This study assessed comfort with and preferences for disability disclosure within healthcare settings among individuals with developmental disabilities and caregivers of individuals with developmental disabilities. Methods An exploratory qualitative research design was employed, utilizing semi-structured interviews with 22 participants (10 patients and 12 caregivers) in South Florida. Data were transcribed and analyzed through thematic analysis to identify key themes related to disability disclosure in healthcare settings. Results Five main themes emerged. Two themes centered on the downside of disclosure (harm avoidance and disclosure utility), while two themes illuminated the upside of disclosure (disclosure necessity and reduced stigma). The final theme focused on disclosure preferences. Conclusions Comfort with disability disclosure among patients and caregivers was largely motivated by a desire to avoid perceived pitfalls and secure quality healthcare. Findings confirm the persistence of inadequate healthcare delivered to patients with disabilities, and the beneficial role disability disclosure can play in addressing current deficiencies. With support of healthcare system leadership and other salient stakeholder groups, further research can inform development, implementation, and evaluation of disclosure systems that facilitate equitable care delivery and improve health outcomes among patients with developmental disabilities.